Effect of micro jet control on the flow filed of the duct at Mach 1.5 - Khan, Sher Afghan; Aabid, Abdul; Mokashi, Imran; Ahmad, Zaheer (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This article reports the outcome of the wind-tunnel investigation on the role of microjets as an active control on the wall pressure distribution. Four tiny jets of 1 mm diameter located at 90-degree intervals along a pcd of 1.3 are employed for the control. The Mach number considered for suddenly expanded flow through the nozzle is 1.5, and the microjets are expanded suddenly into a duct at the base with an area ratio of 3.24 times the CD nozzle exit area. The L/D ratio of the duct was reduced from 10 to 1 in steps of 1. The nozzle pressure ratio (NPR) was operated at 3 to 11 with and without control. The wall pressure distribution is observed in the suddenly expanded axis-symmetric duct. From the results, it has been found that the wall pressure distribution does not adversely influence the microjet controller